How to find the Gateaux differential of this functional?

In summary: Yes, that's correct. Now, to evaluate it you would use the fundamental theorem of calculus and the chain rule repeatedly. For example, I'll do one bit in detail and then leave the rest for you to work out (I'm assuming you know how to differentiate ##(y + \tau \psi)^2## with respect to \tau).$$\frac{d}{d\tau} \int_a^b (y(x) + \tau \psi(x))^2\,dx = \int_a^b \frac{\partial}{\partial \tau} (y(x) + \tau \psi(x))^2\,dx = \int_a^b 2(y(x) + \tau \psi(x
  • #1
Math100
807
227
Homework Statement
Let ## a<b, A ## and ## B ## be constants.
Find the Gateaux differential of the functional ## S[y]=\int_{a}^{b}(y'^{2}+\omega^{2}y^{2}+2yx^{4})dx, y(a)=A, y(b)=B ##, where ## \omega ## is a positive constant.
Relevant Equations
Suppose ## X ## and ## Y ## are locally convex topological vector spaces, ## U\subseteq X ## is open, and ## F: X\rightarrow Y ##. The Gateaux differential ## dF(u; \psi) ## of ## F ## at ## u\in U ## in the direction ## \psi\in X ## is defined as ## dF(u; \psi)=\lim_{\tau\rightarrow 0}\frac{F(u+\tau\psi)-F(u)}{\tau}=\frac{d}{d\tau}F(u+\tau\psi)\biggr\rvert_{\tau=0} ##. If the limit exists for all ## \psi\in X ##, then one says that ## F ## is Gateaux differentiable at ## u ##.
I am not sure if this is correct, but here is my work by using the definition of the Gateaux differential:
\begin{align*}
&dS(y; \psi)=\lim_{\tau\rightarrow 0}\frac{S(y+\tau\psi)-S(y)}{\tau}=\frac{d}{d\tau}S(y+\tau\psi)\biggr\rvert_{\tau=0}\\
&S(y+\tau\psi)=\int_{a}^{b}[(y+\tau\psi)'^{2}+\omega^{2}(y+\tau\psi)^{2}+2(y+\tau\psi)x^{4}]dx\\
&=[(y+\tau\psi)'^{2}x+\omega^{2}(y+\tau\psi)^{2}x+\frac{2}{5}(y+\tau\psi)x^{5}]_{a}^{b}\\
&=(y+\tau\psi)'^{2}(b-a)+\omega^{2}(y+\tau\psi)^{2}(b-a)+[\frac{2}{5}(y+\tau\psi)](b^{5}-a^{5})\\
\end{align*}
Thus ## S(y+\tau\psi)\biggr\rvert_{\tau=0}=y'^{2}(b-a)+\omega^{2}y^{2}(b-a)+\frac{2}{5}y(b^{5}-a^{5}) ##.
So ## \frac{d}{d\tau}S(y+\tau\psi)\biggr\rvert_{\tau=0}=0 ##.

Can anyone please check/verify/confirm this?
 
Physics news on Phys.org
  • #2
Math100 said:
Homework Statement:: Let ## a<b, A ## and ## B ## be constants.
Find the Gateaux differential of the functional ## S[y]=\int_{a}^{b}(y'^{2}+\omega^{2}y^{2}+2yx^{4})dx, y(a)=A, y(b)=B ##, where ## \omega ## is a positive constant.
Relevant Equations:: Suppose ## X ## and ## Y ## are locally convex topological vector spaces, ## U\subseteq X ## is open, and ## F: X\rightarrow Y ##. The Gateaux differential ## dF(u; \psi) ## of ## F ## at ## u\in U ## in the direction ## \psi\in X ## is defined as ## dF(u; \psi)=\lim_{\tau\rightarrow 0}\frac{F(u+\tau\psi)-F(u)}{\tau}=\frac{d}{d\tau}F(u+\tau\psi)\biggr\rvert_{\tau=0} ##. If the limit exists for all ## \psi\in X ##, then one says that ## F ## is Gateaux differentiable at ## u ##.

I am not sure if this is correct, but here is my work by using the definition of the Gateaux differential:
\begin{align*}
&dS(y; \psi)=\lim_{\tau\rightarrow 0}\frac{S(y+\tau\psi)-S(y)}{\tau}=\frac{d}{d\tau}S(y+\tau\psi)\biggr\rvert_{\tau=0}\\
&S(y+\tau\psi)=\int_{a}^{b}[(y+\tau\psi)'^{2}+\omega^{2}(y+\tau\psi)^{2}+2(y+\tau\psi)x^{4}]dx\\
&=[(y+\tau\psi)'^{2}x+\omega^{2}(y+\tau\psi)^{2}x+\frac{2}{5}(y+\tau\psi)x^{5}]_{a}^{b}\\
&=(y+\tau\psi)'^{2}(b-a)+\omega^{2}(y+\tau\psi)^{2}(b-a)+[\frac{2}{5}(y+\tau\psi)](b^{5}-a^{5})\\
\end{align*}
Thus ## S(y+\tau\psi)\biggr\rvert_{\tau=0}=y'^{2}(b-a)+\omega^{2}y^{2}(b-a)+\frac{2}{5}y(b^{5}-a^{5}) ##.
So ## \frac{d}{d\tau}S(y+\tau\psi)\biggr\rvert_{\tau=0}=0 ##.

Can anyone please check/verify/confirm this?
I'm not all that familiar with the Gateaux differential.

It seems to me that you need to first do the differentiation, ##\dfrac{d}{d\tau} S(y+\tau\psi)##, then evaluate the result at ##\tau =0##.
 
  • #3
Math100 said:
Homework Statement:: Let ## a<b, A ## and ## B ## be constants.
Find the Gateaux differential of the functional ## S[y]=\int_{a}^{b}(y'^{2}+\omega^{2}y^{2}+2yx^{4})dx, y(a)=A, y(b)=B ##, where ## \omega ## is a positive constant.
Relevant Equations:: Suppose ## X ## and ## Y ## are locally convex topological vector spaces, ## U\subseteq X ## is open, and ## F: X\rightarrow Y ##. The Gateaux differential ## dF(u; \psi) ## of ## F ## at ## u\in U ## in the direction ## \psi\in X ## is defined as ## dF(u; \psi)=\lim_{\tau\rightarrow 0}\frac{F(u+\tau\psi)-F(u)}{\tau}=\frac{d}{d\tau}F(u+\tau\psi)\biggr\rvert_{\tau=0} ##. If the limit exists for all ## \psi\in X ##, then one says that ## F ## is Gateaux differentiable at ## u ##.

I am not sure if this is correct, but here is my work by using the definition of the Gateaux differential:[tex]
\begin{align*}
&dS(y; \psi)=\lim_{\tau\rightarrow 0}\frac{S(y+\tau\psi)-S(y)}{\tau}=\frac{d}{d\tau}S(y+\tau\psi)\biggr\rvert_{\tau=0}\\
&S(y+\tau\psi)=\int_{a}^{b}[(y+\tau\psi)'^{2}+\omega^{2}(y+\tau\psi)^{2}+2(y+\tau\psi)x^{4}]dx\\
&=[(y+\tau\psi)'^{2}x+\omega^{2}(y+\tau\psi)^{2}x+\frac{2}{5}(y+\tau\psi)x^{5}]_{a}^{b}
\end{align*} [/tex]

No. [itex]y[/itex] and [itex]\psi[/itex] are arbitrary functions of [itex]x[/itex] satisfying [itex]y(a) = A[/itex], [itex]y(b) = B[/itex] and [itex]\psi(a) = \psi~(b) = 0[/itex]. You can't actually evaluate the integral because you don't know what [itex]y[/itex] and [itex]\psi[/itex] are. Instead you must bring the differentiation with respect to [itex]\tau[/itex] inside the integral, where it becomes a partial derivative at constant [itex]x[/itex].
 
  • Like
Likes SammyS
  • #4
pasmith said:
No. [itex]y[/itex] and [itex]\psi[/itex] are arbitrary functions of [itex]x[/itex] satisfying [itex]y(a) = A[/itex], [itex]y(b) = B[/itex] and [itex]\psi(a) = \psi~(b) = 0[/itex]. You can't actually evaluate the integral because you don't know what [itex]y[/itex] and [itex]\psi[/itex] are. Instead you must bring the differentiation with respect to [itex]\tau[/itex] inside the integral, where it becomes a partial derivative at constant [itex]x[/itex].
Do you mean ## S(y+\tau\psi)=\int_{a}^{b}\frac{d}{d\tau}(y'^{2}+\omega^{2}y^{2}+2yx^{4})dx ##? If so, then how to evaluate this?
 
  • #5
Math100 said:
Do you mean ## S(y+\tau\psi)=\int_{a}^{b}\frac{d}{d\tau}(y'^{2}+\omega^{2}y^{2}+2yx^{4})dx ##? If so, then how to evaluate this?

[tex]\begin{split}
S[y + \tau \psi] &= \int_a^b (y(x)' + \tau \psi(x)')^2 + \omega^2(y(x) + \tau\psi(x))^2 + 2(y(x) + \tau \psi(x))x^4\,dx \\
\left.\frac{d}{d\tau} S[y + \tau \psi]\right|_{\tau=0} &=
\int_a^b \left.\frac{\partial}{\partial \tau}\left(((y'(x) + \tau\psi'(x))^2 + \omega^2(y(x) + \tau\psi(x))^2 + 2(y(x) + \tau\psi(x))x^4\right)\right|_{\tau=0}\,dx. \end{split}[/tex] Again, you need to calculate the (partial) derivative with respect to [itex]\tau[/itex] and then set [itex]\tau = 0[/itex]. [itex]\left.\dfrac{df}{dt}\right|_{t=t_0}[/itex] is how we indicate where the derivative is to be evaluated using Leibnitz's notation; with Newton's notation we would just write [itex]f'(t_0)[/itex].
 
Last edited:
  • #6
pasmith said:
[tex]\begin{split}
S[y + \tau \psi] &= \int_a^b (y(x)' + \tau \psi(x)')^2 + \omega^2(y(x) + \tau\psi(x))^2 + 2(y(x) + \tau \psi(x))x^4\,dx \\
\left.\frac{d}{d\tau} S[y + \tau \psi]\right|_{\tau=0} &=
\int_a^b \left.\frac{\partial}{\partial \tau}\left(((y'(x) + \tau\psi'(x))^2 + \omega^2(y(x) + \tau\psi(x))^2 + 2(y(x) + \tau\psi(x))x^4\right)\right|_{\tau=0}\,dx. \end{split}[/tex] Again, you need to calculate the (partial) derivative with respect to [itex]\tau[/itex] and then set [itex]\tau = 0[/itex]. [itex]\left.\dfrac{df}{dt}\right|_{t=t_0}[/itex] is how we indicate where the derivative is to be evaluated using Leibnitz's notation; with Newton's notation we would just write [itex]f'(t_0)[/itex].
After breaking down into smaller pieces, I got the following:
\begin{align*}
&(y'(x)+\tau\psi'(x))^{2}=y'^{2}(x)+2y'(x)\tau\psi'(x)+\tau^{2}\psi'^{2}(x)\\
&\omega^{2}(y(x)+\tau\psi(x))^{2}=\omega^{2}y^{2}(x)+2\tau\psi(x)\omega^{2}+\omega^{2}\tau^{2}\psi^{2}(x)\\
&2(y(x)+\tau\psi(x))x^{4}=2x^{4}y(x)+2x^{4}\tau\psi(x)\\
&\frac{d}{d\tau}[(y(x)'+\tau\psi(x)')^{2}]=2y'(x)\psi'(x)+2\tau\psi'^{2}(x)\\
&\frac{d}{d\tau}[\omega^{2}(y(x)+\tau\psi(x))^{2}]=2\psi(x)\omega^{2}+2\omega^{2}\tau\psi^{2}(x)\\
&\frac{d}{d\tau}[2(y(x)+\tau\psi(x))x^{4}]=2x^{4}\psi(x)\\
\end{align*}
So
\begin{align*}
&\frac{d}{d\tau}S[y+\tau\psi]_{\tau=0}\\
&=[2y'(x)\psi'(x)+2\tau\psi'^{2}(x)+2\psi(x)\omega^{2}+2\omega^{2}\tau\psi^{2}(x)+2x^{4}\psi(x)]_{\tau=0}\\
&=2y'(x)\psi'(x)+2\psi(x)\omega^{2}+2x^{4}\psi(x).\\
\end{align*}
Thus
\begin{align*}
&\int_{a}^{b}[2y'(x)\psi'(x)+2\psi(x)\omega^{2}+2x^{4}\psi(x)]dx\\
&=[2xy'(x)\psi'(x)+2x\psi(x)\omega^{2}+\frac{2}{5}x^{5}\psi(x)]_{a}^{b}\\
&=[2by'(x)\psi'(x)+2b\psi(x)\omega^{2}+\frac{2}{5}b^{5}\psi(x)]-[2ay'(x)\psi'(x)+2a\psi(x)\omega^{2}+\frac{2}{5}a^{5}\psi(x)]\\
&=(b-a)(2y'(x)\psi'(x)+2\psi(x)\omega^{2})+(b^{5}-a^{5})(\frac{2}{5}\psi(x)).\\
\end{align*}
Thus
\begin{align*}
&\frac{d}{d\tau}S[y+\tau\psi]_{\tau=0}=(b-a)(2y'(x)\psi'(x)+2\psi(x)\omega^{2})+(b^{5}-a^{5})(\frac{2}{5}\psi(x)).\\
\end{align*}
Is this correct?
 
  • #7
Math100 said:
After breaking down into smaller pieces, I got the following:
\begin{align*}
&(y'(x)+\tau\psi'(x))^{2}=y'^{2}(x)+2y'(x)\tau\psi'(x)+\tau^{2}\psi'^{2}(x)\\
&\omega^{2}(y(x)+\tau\psi(x))^{2}=\omega^{2}y^{2}(x)+2\tau\psi(x)\omega^{2}+\omega^{2}\tau^{2}\psi^{2}(x)\end{align*}

You are missing a [itex]y(x)[/itex] from the second term on the right on the last line. But it is easier to use the chain rule rather than multiply everything out: [tex]\frac{\partial}{\partial \tau} (y(x) + \tau \psi(x)')^2 = 2(y'(x) + \tau \psi'(x))\psi'(x)[/tex] etc.

Thus
\begin{align*}

&\int_{a}^{b}[2y'(x)\psi'(x)+2\psi(x)\omega^{2}+2x^{4}\psi(x)]dx\\

&=[2xy'(x)\psi'(x)+2x\psi(x)\omega^{2}+\frac{2}{5}x^{5}\psi(x)]_{a}^{b}\\

&=[2by'(x)\psi'(x)+2b\psi(x)\omega^{2}+\frac{2}{5}b^{5}\psi(x)]-[2ay'(x)\psi'(x)+2a\psi(x)\omega^{2}+\frac{2}{5}a^{5}\psi(x)]\\

&=(b-a)(2y'(x)\psi'(x)+2\psi(x)\omega^{2})+(b^{5}-a^{5})(\frac{2}{5}\psi(x)).\\

\end{align*}

Aside from the factor of [itex]y(x)[/itex] missing from the second term, the first line is essentially correct. But the rest is wrong. You have a definite integral with respect to [itex]x[/itex]; its value should therefore not depend on [itex]x[/itex], but should be a function of the limits [itex]a[/itex] and [itex]b[/itex]. However, you can't evaluate the integral since you don't know how the integrand depends on [itex]x[/itex] (because you don't know what [itex]y[/itex] and [itex]\psi[/itex] are). It is not in general true that [itex]\int_a^b xy(x)\,dx = by(b) - ay(a)[/itex].

The most you can do is integrate the first term by parts to get [tex]
\int_a^b 2y'(x)\psi'(x) + 2\omega^2y(x)\psi(x) + 2x^4 \psi(x)\,dx = 2 \int_a^b \left(-y''(x) + \omega^2y(x) + x^4\right)\psi(x)\,dx + 2\left[y'(x)\psi(x)\right]_a^b[/tex] but that is as far as you can go.
 
  • Like
Likes SammyS

Similar threads

Back
Top